The market as a mechanism for conflict resolution: the case of Ecuador - Reátegui, Rubén Méndez; Lescano, Viviana; Mena, Mayra (REVISTA PROCESOS DE MERCADO, 2017)
Efficacy, efficiency, and effectiveness are pillars in the field of law primarily referred to when the discussion focuses on access and the service of providing justice. As discussed by Landero (2014)1, conflict resolutions by means of alternative mechanisms, such as mediation, under the institutional framework, constitute guaran-tees to be respected in processes for which the provision may affect the rights of individuals. This has been well pointed out in Article 8 of the American Convention on Human Rights (2001)2, which regulates judicial guarantees and Article 14 of the International Covenant on Civil and Political Rights. Also, as intrinsic values of the legal system, the efficacy, efficiency and effectiveness have been extensively studied by doctrine contributions from Calsami-glia (1987)3, Paz-Ares and Valencia (1995)4, Mercuro and Medema (1998)5, Zywicki and Stringham (2010)6. However, presenting them operatively in a way that is related to how the evaluation mecha-nism is applied in order to have a better picture of the resolution of conflicts outside of court such as those confined within the field of childhood and adolescence through the market represents a novel contribution. In other words, it is a contribution that will assess the regressive performance (judged) compared to what is obtained by private instruments (mediation centers). The evaluation of alternative justice, specifically mediation for a diagnosis of the performance of this justice, and to contrast it with the trial, allows for mistakes and successes in the develop-ment of service justice in relation to the mechanisms for the reso-lution of conflicts outside of court in cases of childhood and adolescence as a starting point for subsequent evaluations. The guidelines state, specifically with regard to effective mediation, mediation initiatives that are improvised and uncoordinated by states but are launched with the best of intentions, do not contrib-ute to the objective of raising institutional barriers that limit the spontaneous appearance of a culture of peace and non-aggression for which the processes must have strong technical and financial support. In light of this, Marquez (2012)7 evaluated mediation in court, employing the “criteria” that he called; Efficacy, Efficiency and Effectiveness. Although the methodology that was introduced was similar to that of this document, Marquez (2012) defends the role of the state by arguing that it does not conceptualize the crite-ria, and definitions given for the right to mediation should not focus on the issues of resolving conflicts outside of court in cases of childhood and adolescence.